OPS: a fairness link allocation based on SDN in datacentre networks. (5th May 2020) - Kao, Tain-Lieng; Miao, Yan Ting; Wang, San-Yuan
Nowadays, redundant topologies with multiple forwarding paths between original-destination (OD) pairs have been proposed for datacentre networks, such as fat-tree topology. To achieve resultant fairness (fair utilisation) in this topology, previous algorithms were based on traditional shortest path algorithms or equal-cost multiple paths algorithms (ECMP). However, these algorithms are facing with take up a lot of resources of the SDN controller and may cause a large amount of loss of resultant fairness for the network that has different configurations of link capacity. In this paper, we present out port selection (OPS) mechanisms, including modular out port selection (MOPS) and random out port selection (ROPS), novel methods to improve resultant fairness of fat-tree topology SDN-based datacentre network. Compare with static load-balance methods, our MOPS and ROPS can reduce 65% and 33% loss of fairness, respectively. Further, combining with elephant flows detecting and handling mechanisms, MOPSE and ROPSE can dynamically assign better forwarding path for elephant flows.